METODOLOGICAL FOUNDATIONS OF DEVELOPING COMMUNICATIVE COMPETENCE IN THE EDUCATION SYSTEM OF UZBEKISTAN - Aliqulova Feruza O‘ktam qizi (The Conference Hub, 2025)
This article examines the methodological foundations of developing communicative competence in the education system of Uzbekistan. The communicative approach is a key component of modern foreign language education reforms, particularly in line with the national competency-based curriculum and international frameworks such as CEFR. The study reviews theoretical principles, state policy documents, and practical classroom strategies aimed at fostering communicative skills among learners. It highlights the role of interactive tasks, integration of digital technologies, and culturally oriented content in shaping effective communicative competence. The article concludes that methodological innovation and teacher training are essential for aligning Uzbekistan’s education system with global standards.
Keywords: communicative competence, competency-based education, Uzbekistan, methodology, CEFR, interactive learning